2022
DOI: 10.1109/access.2022.3207772
|View full text |Cite
|
Sign up to set email alerts
|

Buildings Participation in Resilience Enhancement of Community Microgrids: Synergy Between Microgrid and Building Management Systems

Abstract: Military bases, communities, and university-scale microgrids are being implemented to serve critical loads of high priority. Remote switch scheduling and distributed energy resources (DERs) operation strategies for post-disaster service restoration have been explored in previous literature. Flexible buildings offer the central microgrid management system an opportunity to ensure available energy is directed to the critical loads. This work presents a novel bi-level optimal sequence of operations for managing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Figure (9) illustrates a comparison between the initial network loads and the changed loads in the demand-side management program. As can be seen, the peak load has been reduced in the demand side management program.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure (9) illustrates a comparison between the initial network loads and the changed loads in the demand-side management program. As can be seen, the peak load has been reduced in the demand side management program.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In [8], a framework based on an integrated stochastic optimization model has been proposed for joint operation and maintenance in a multimicrogrid environment, with the objective of enhancing resilience. In [9], an approach based on mixed integer linear programming (MILP) has been proposed for enabling buildings to participate in enhancing microgrid resilience by leveraging synergies between microgrid and building management systems. In [10], a generic method based on AC load flow is proposed for optimizing networks by incorporating distributed energy resources, with the objective of reducing power losses.…”
Section: A Background Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…THHN and TFFN are two types of electrical wiring that are commonly used in PMA construction. THHN stands for Thermoplastic High Heat-Resistant Nylon-Coated, and it is a type of single conductor electrical wire [11,54]. It is rated for 600 volts and 90 • C, and it is designed to withstand high temperatures.…”
Section: Permanent Magnet Alternatormentioning
confidence: 99%
“…-Owolabi et al [4] analyzed mono crystalline type has better yield compared with poly crystalline type silicon panels for the PV system located in South Korea. -Chamana et al [5] using mixed-integer linear programming (MILP) model and controller hardware inloop (CHIL) using resilience-oriented optimization algorithm, different micro grid types are implemented to serve critical loads at high priority like building level energy management under emergency conditions at military bases. -Masrur et al [6] analyzed techno-economic evaluations like net present value (NPC) levelized cost of energy (LOCE) for optimally tilted PV system located at Hatiya, Bangladesh, and concluded that the power exchange cost is lower than the value of the derating factor.…”
Section: Introductionmentioning
confidence: 99%